2009
DOI: 10.1038/hr.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of albuminuria by different blood pressure measurement methods in type 1 diabetes: a pilot study

Abstract: In type 1 diabetes, the risk of nephropathy is strongly influenced by the level of blood pressure (BP). Ambulatory BP (ABP) monitoring has revealed an association between disturbed nocturnal BP drop and albuminuria and suggested a role of BP in microalbuminuria development. This study investigated the relationship between the urinary albumin excretion ratio (AER) and home BP (HBP) compared with ABP and clinical BP (CBP) measurements. A total of 50 adolescents and young adults with type 1 diabetes without hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
(57 reference statements)
1
8
0
2
Order By: Relevance
“…In agreement with previous studies, we found that hypertensive individuals were at high risk for MAU, with blood pressure linearly associated with MAU [ 12 , 24 , 28 , 29 ]. A recent national hypertension survey in China found that blood pressure was controlled under 140/90 mmHg in 9.3% of hypertensive individuals [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies, we found that hypertensive individuals were at high risk for MAU, with blood pressure linearly associated with MAU [ 12 , 24 , 28 , 29 ]. A recent national hypertension survey in China found that blood pressure was controlled under 140/90 mmHg in 9.3% of hypertensive individuals [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In diabetic hypertensive patients, concentric and eccentric left ventricular hypertrophy, increase in left ventricular muscle mass have been documented . In DM, the relationship between ABPM measurements and target organ damage has been showed in studies performed especially in adults . In this study, we planned to examine the relationship between elevated BP in diabetic children and early cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Mobilograph (I.E.M., Stolberg, Germany) was programmed to measure BP at 20‐min intervals from 08:00 to 23:00 hours and at 30‐min intervals from 23:00 to 08:00 hours . ABPM data with less than 30 valid daytime BP measurements and/or less than 12 valid nighttime measurements were not included .…”
Section: Methodsmentioning
confidence: 99%
“…SBP has been demonstrated to independently determine cIMT in both children and adolescents . Changes in vascular function also occur at higher levels of childhood BP, including reduced brachial artery distensibility, higher PWV, and increased AIx, all of which indicate increasing arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…37 SBP has been demonstrated to independently determine cIMT in both children 38 and adolescents. 39 Changes in vascular function also occur at higher levels of childhood BP, including reduced brachial artery distensibility, 40,41 higher PWV, 42,43 and increased AIx, 44 all of which indicate increasing arterial stiffness. This is relevant to future cardiovascular disease, because increased vascular thickness 45 and stiffness 46 are associated with higher LVM in adolescents, a risk factor for future adult cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%